Hiding in Plain Sight: Co-Enacting the Sustainable Worker Schema in a Consulting Firm - Heaphy, Emily D.; Trefalt, Špela (Organization Science, 2024)
This inductive study of 44 consultants in a prominent consulting firm examines how consultants set work-life boundaries without getting stigmatized and how they develop their workplace relationships into sources of help for this process. Within this organization, dominated by the ideal worker norm, we found a hidden, self-sustaining network of consultants who delivered excellent work while violating the ideal worker norm without stigmatization. Their way of working was based on a coherent set of beliefs about work and the work-life interface we named the sustainable worker schema, which contrasted with the ideal worker schema in all ways except in the ultimate goals: high performance and excellent work. Essential to this way of working was not only effective management of boundaries between work and life outside of work (work-life boundaries) but also effective management of boundaries around each work task or project (work boundaries). Consultants who embraced the sustainable worker schema worked fewer hours and achieved higher satisfaction with work-life balance than their counterparts. Together, these findings highlight the importance of embracing the centrality of work in work-life research; underscore the power of invisibility when challenging the ideal worker norm; and paint a rich picture of boundary work as a network-level phenomenon. Funding: This work was supported by Simmons University [Diane K. Trust Chair in Leadership Development, President’s Fund for Faculty Excellence] and University of Massachusetts Amherst [John F. Kennedy Faculty Fellowship].